2014
DOI: 10.1093/ijnp/pyu028
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Exposure Induces Neonatal Neurodegeneration by Enhancing CB1R Exon1 Histone H4K8 Acetylation and Up-regulating CB1R Function causing Neurobehavioral Abnormalities in Adult Mice

Abstract: Background:Ethanol exposure to rodents during postnatal day 7 (P7), which is comparable to the third trimester of human pregnancy, induces long-term potentiation and memory deficits. However, the molecular mechanisms underlying these deficits are still poorly understood.Methods:In the present study, we explored the potential role of epigenetic changes at cannabinoid type 1 (CB1R) exon1 and additional CB1R functions, which could promote memory deficits in animal models of fetal alcohol spectrum disorder.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
112
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(118 citation statements)
references
References 101 publications
6
112
0
Order By: Relevance
“…In addition to increased AEA and associated biosynthetic enzymes, the alcohol‐induced transcriptional activation of the Cnr1 gene results in increased levels of Cnr1 mRNA and CB 1 receptor protein expression in cortical and hippocampal brain regions (Subbanna, Shivakumar, Psychoyos, Xie, & Basavarajappa, ). Remarkably, we found that postnatal alcohol exposure in mice enhances the acetylation of histone (H4) on Lys 8 (H4K8ace) in exon 1 of Cnr1 and CB 1 receptor binding and CB 1 receptor agonist‐stimulated GTPγS binding in cortical and hippocampal brain regions (Subbanna, Nagre, Umapathy, Pace, & Basavarajappa, ). The administration of SR or the genetic ablation of CB 1 receptors (CB 1 −/− ) before alcohol exposure prevents neuronal cell death (Subbanna et al, ; Subbanna et al, ).…”
Section: The Role Of the Ecb System During Development And Its Functimentioning
confidence: 99%
“…In addition to increased AEA and associated biosynthetic enzymes, the alcohol‐induced transcriptional activation of the Cnr1 gene results in increased levels of Cnr1 mRNA and CB 1 receptor protein expression in cortical and hippocampal brain regions (Subbanna, Shivakumar, Psychoyos, Xie, & Basavarajappa, ). Remarkably, we found that postnatal alcohol exposure in mice enhances the acetylation of histone (H4) on Lys 8 (H4K8ace) in exon 1 of Cnr1 and CB 1 receptor binding and CB 1 receptor agonist‐stimulated GTPγS binding in cortical and hippocampal brain regions (Subbanna, Nagre, Umapathy, Pace, & Basavarajappa, ). The administration of SR or the genetic ablation of CB 1 receptors (CB 1 −/− ) before alcohol exposure prevents neuronal cell death (Subbanna et al, ; Subbanna et al, ).…”
Section: The Role Of the Ecb System During Development And Its Functimentioning
confidence: 99%
“…Genetic deletion of Tet1 impairs several synaptic plasticity-related genes, including Arc, and induces abnormal hippocampal synaptic plasticity and impaired spatial [116] and contextual fear memory [117]. Although future studies are required to understand the brain region specific epigenome changes and their relationship to observed neurobehavioral deficits in adult animals, our studies clearly suggest that the impairment of DNA methylation during early brain development affects the expression of survival factors [118] such as Arc [23] expression, inducing a delay in neuronal maturation [119]. Moreover, such impairment may be responsible for the observed object, spatial and social recognition memory deficits and synaptic plasticity abnormalities in adult mice.…”
Section: Discussionmentioning
confidence: 98%
“…Our findings suggest that the mechanism by which 5-AzaC induces caspase-3 activation differs significantly from that of alcohol-induced caspase-3 activation in P7 mice [9]. This is partly because pre-administration of a G9a/GLP inhibitor (Bix) [22, 35] or CB1R antagonist (SR) [19, 23, 24], which are known to prevent alcohol-induced caspase-3 activation, failed to rescue 5-AzaC-induced caspase-3 activation in neonatal mice. Furthermore, the CB1RKO, which provides protection against alcohol-induced caspase-3 activation [19, 23, 24], also failed to rescue 5-AzaC-induced caspase-3 activation in neonatal mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations